MELAMPAUI TERORISME: PENDEKATAN KOMPREHENSIF UNTUK MEMAHAMI DAN MENANGKAL TERORISME - Reza Antonius Watimena , Bustanul Arifin (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
This study aims to formulate the steps and strategies that must be done to deal with the growing terrorism problem in the early 21st century. This research will analyze the underlying causes and reasons for the emergence of terrorism which then becomes a serious challenge for the international community, especially Indonesia. As for the background of this research is the development of terrorism is increasingly rapid and fertile that threatens the stability and integrity of a country. Why is terrorism growing more fertile? Is there anything wrong with the efforts and strategies that have been used so far? And, should new approaches and ways to be used to counter terrorism? These questions form the basis for the author to explore more deeply about the dynamics of terrorism with examples of countries such as Indonesia. The narrow mindset of individuals and groups, as well as the lack of critical thinking about the information or development of life seen, and the failure of love, have led them to a radical understanding that encourages terrorists. Thus, in this study, transcendence can be a fundamental way to change the root causes of individuals or groups in becoming radical. The transcendence must be followed by comprehensive approaches from the government, society, as well as changes in social circumstances, particularly economy and education